"You may quite well say that we are all ill": Freud on the continuity between normality and pathology. (April 2020) - Petrolini, Valentina
The relation between normality and pathology has intrigued philosophers for centuries, but it has been recently revived by a number of researchers who have articulated and defended various versions of the continuity thesis (or CT, namely the idea that normal and pathological states are not categorically different). Despite a growing interest in the notion of continuity, CT is far from being the received view within philosophy of psychiatry, with many researchers still seeing normal and pathological states as being different in kind. In this article, I show that the core ideas underlying CT were already present in a sophisticated form in Freud's work. Indeed, Freud defends two interrelated theses that allow us to see him as an early defender of continuity. On the one hand, he is committed to the idea that healthy and mentally disordered subjects exhibit deep similarities in terms of mental functioning. On the other hand, he defends the possibility of describing with sufficient precision and generality what goes awry in pathological cases. The article is structured as follows: I first appeal to Freud's work to show that his account of psychopathology supports continuity; I then focus on two theoretical aspects of Freud's proposal that should be taken as desiderata for any refined account of mental disorders; and finally, I illustrate how the approach works in practice by analyzing one of Freud's clinical cases.